DESCRIPTION OF THE CONCEPT «MORAL VALUES OF PERSONALITY» - Fedorova, Mariya A. (Educological discourse, 2014)
The article deals with the nature of the concept "values" in humanities, examines the classification of values, analyzes the peculiarities of functioning, pedagogical conditions, forms and methods of moral values upbringing. The article highlights the structure of moral values of pre-school aged children and primary school aged children,states criteria and figures of moral values.